Sufi Hermeneutics and Symbolic Tafsir in the Javanese Manuscript Hakikate Bismillah - Mauluddin, Moh.; Firdaus, Moh. Fiqih; Munir, Misbahul; Azkiyah, Ulfa Mina (UIN Sunan Kalijaga Yogyakarta, 2025)
The exploration of Qur'anic commentaries rooted in the Islamic traditions of the Nusantara offers valuable insight into the development of a more contextually and spiritually hermeneutic framework. This study focuses on Hakikate Bismillah, a Sufi-influenced tafsir manuscript composed in Javanese-Pegon script and originating from a pesantren in Lamongan, East Java. Through symbolic and experiential readings, the manuscript articulates a mystical interpretation of the phrase Bismillāhirraḥmānirraḥīm, grounded in inner reflection and spiritual awareness. At the heart of this research is an effort to uncover the esoteric interpretive structure underlying the text and to analyze its synthesis with classical Sufi hermeneutics and Javanese cosmological thought. The study employs a qualitative-descriptive methodology, with content analysis serving as the central analytical instrument. This is complemented by a selective philological examination of the manuscript and informed by key works in the Sufi tradition, particularly those of Ibn ʿArabī, al-Qushayrī, and al-Ghazālī. A comparative lens is also applied to situate Hakikate Bismillah within the broader landscape of local Qur'anic exegesis across the Indonesian archipelago. Primary data are sourced from a digitized copy of the manuscript preserved in the British Library collection (EAP061/2/65), alongside secondary literature in both Sufi exegesis and Javanese metaphysical texts. Analysis reveals that the constituent syllables bis, mil, and lah in the word bismillah are interpreted as progressive spiritual stations, īmān (faith), tawḥīd (divine oneness), and maʿrifah (gnosis), respectively. These are intricately tied to the concept of ati, the Javanese term corresponding to the Arabic qalb (spiritual heart), regarded as the inner vessel of divine consciousness. This manuscript thus offers a distinctive model of esoteric tafsir that interlaces Sufi metaphysics, Qur'anic semiotics, and localized spiritual cosmology. The study’s principal contribution lies in proposing a hermeneutical paradigm that integrates transcendental insight with cultural particularity, thereby advancing Qur'anic interpretation in directions that are not only interdisciplinary and dialogical, but also deeply transformative.